2006
DOI: 10.1354/vp.43-5-632
|View full text |Cite
|
Sign up to set email alerts
|

Canine Hemophagocytic Histiocytic Sarcoma: A Proliferative Disorder of CD11d+ Macrophages

Abstract: Abstract. Histiocytic disorders of dogs include histiocytoma, localized histiocytic sarcoma (HS), disseminated HS (malignant histocytosis), and the reactive histiocytoses: cutaneous and systemic. A common element to these diseases is proliferation of dendritic cells (DC) of either Langerhans cell (epithelial DC) or interstitial DC lineage. In this report, 17 dogs with hemophagocytic HS are described. Breeds affected included Bernese Mountain Dog (6), Golden Retriever (4), Rottweiler (3), Labrador Retriever (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
273
3
18

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(310 citation statements)
references
References 48 publications
16
273
3
18
Order By: Relevance
“…Some canine histiocytic sarcomas arise from the splenic red pulp and the bone marrow; their immunophenotype and marked hemophagocytic activity indicates a macrophage origin. 26 Histiocytic proliferative diseases are uncommon in cats and their documentation is limited to a few case reports. Most cases were not associated with cutaneous lesions, but presented with internal disease and prominent weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some canine histiocytic sarcomas arise from the splenic red pulp and the bone marrow; their immunophenotype and marked hemophagocytic activity indicates a macrophage origin. 26 Histiocytic proliferative diseases are uncommon in cats and their documentation is limited to a few case reports. Most cases were not associated with cutaneous lesions, but presented with internal disease and prominent weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Some canine histiocytic sarcomas are of macrophage origin and primarily arise in the splenic red pulp or the bone marrow. 26 Histiocytic proliferative diseases are uncommon in cats, and their documentation is limited to a few case reports. 10,[12][13][14]18 The goal of this study was to characterize a histiocytic proliferative disease observed in 30 cats.…”
mentioning
confidence: 99%
“…Provisional pathological criteria for inclusion in the study as possible HHS cases were derived from Moore et al (8). Dogs were selected if the histiocytic tumor cells showed phagocytosis of erythrocytes, a diffuse pattern of tissue involvement, with preferably intra-sinusoidal (liver/lymph nodes) and intravascular spread and involvement of splenic red pulp, while encroaching on the white pulp with only sparse lymphocytic infiltration.…”
Section: Hhs Inclusion Criteriamentioning
confidence: 99%
“…The differential diagnoses for HS are many and include not only almost the entire spectrum of poorly differentiated round cell tumors, but also other histiocytic diseases such as reactive cutaneous/systemic histiocytosis (CH/SH), hemophagocytic syndrome, immune-mediated hemolytic anemia, and granulomatous inflammation (1,(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Esse último possui uma abordagem clinicopatológica diferente, sendo que estudos mostram sua origem no baço, advindas de macrófagos da polpa vermelha que têm origem na medula óssea (MOORE et al, 2006;HENDRICK, 2017;). O sarcoma histiocítico localizado se difere do disseminado quanto à suas características clínicas.…”
Section: Introductionunclassified